Causation of crimes against the security of production - Таран, Олена Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Causation of crimes against the security of production – is objectively existing link between the act (act or omission) (reason) and socially dangerous consequences (consequence), when the act or omission causes (generates) of socially dangerous. Causation is usually complex and indirect nature. This is due to numerous factors that impede its development. To establish the presence (absence) of a causal connection required: 1) to investigate the mechanism of crime; identify intermediate events (events, actions, circumstances) in respect of initial and final; 2) to isolate the intermediate those phenomena (events, actions, circumstances) that are important in general; 3) set the value at the time of intermediate events; 4) mentally consistently eliminate each of them, ranging from close to the result; 5) determine whether the place would have the same result for these exemptions, ie whether this violation could cause harmful effects available in the absence of other events (circumstances, events); 6) investigate all violations that have harmful effects, but not limited to those who have been coming to this result, that take into account the totality of the factors preceding injury; 7) formulate a conclusion about the presence or absence of a causal link, depending on the results obtained.